336WASIAT WAJIBAH SEBAGAI PENEMUAN HUKUM OLEH HAKIM DALAM PERKARA WARIS BEDA AGAMA (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 16 K/AG/2010) - Nurhadi Abdul Gani (Jurnal Hukum dan Peradilan, 2017)
The majority practice of inheritance distribution in the Religious Courts for the heirs of different religions was the nonmuslim heirs are not entitled to the inheritance of their parents, such a verdict is not without a strong foundation, there is a strong basis utterance of Prophet Muhammad SAW which states: “muslim does not inherit a nonmuslim, and a nonmuslim also does not inherit a Muslim". In this research will review two problem formulas. Firstly, is the Supreme Court's decision a legal breakthrough or legal invention? Secondly, is the legal instrument of granting inheritance rights to nonmuslim families through a wajibah wasiyah considered appropriate. The method used in this research is analytical descriptive. The results of the research indicate that the Supreme Court Decision Number 16 K/AG/2010 can be considered as legal invention in the division of inheritance for the heirs of different religions, without violating the hadith provisions. The instrument used in inheritance distribution toward nonmuslim is right with wajibah wasiyah.Keywords: inheritance, wajibah wasiyah, nonmuslim